Hepatic steatosis and respiratory diseases: a new panorama - Alan Eduardo Botello-Manilla; Guillermo Nahúm López-Sánchez; Norberto Carlos Chávez-Tapia; Misael Uribe; Natalia Nuño-Lámbarri (Annals of Hepatology, 2021)
Non-alcoholic fatty liver disease is defined as hepatic fat accumulation in more than 5% of hepatocytes, without other liver steatosis causes. It comprises a broad spectrum that can range from benign steatosis and progress to non-alcoholic steatohepatitis, fibrosis, and ultimately hepatocellular carcinoma. Non-alcoholic fatty liver is considered a multisystemic disease since it is related to multiple disorders, such as type 2 diabetes mellitus, polycystic ovary syndrome, chronic kidney disease, psoriasis, osteoporosis, hypothyroidism, cardiovascular diseases, and obstructive sleep apnea syndrome; it is becoming increasingly clear that it is also a risk factor for developing certain respiratory diseases. This article aims to understand the liver and chronic obstructive pulmonary disease mechanisms, obstructive sleep apnea syndrome, asthma, and lung cancer. Given that non-alcoholic fatty liver disease has a considerable impact on the patient’s well-being and life quality, as well as on the costs they generate for the country’s health services, it is essential to continue research, especially in areas such as the respiratory tract, as there is much misinformation about it.